2004
DOI: 10.1002/macp.200300123
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Epoxidized Styrene‐Butadiene Block Copolymers as Templates for Nanostructured Thermosets

Abstract: Summary: A wide range of epoxidized styrene‐block‐butadiene block copolymers were synthesized using hydrogen peroxide in the presence of an in situ prepared methyltrioctylammoniumtetrakis(diperoxotungstate)phosphate as the catalyst system in a water/dichloroethane biphasic system. 1H NMR and FT‐IR spectra revealed that the epoxidation procedure led mainly to 1,4‐epoxidized butadiene units. GPC analysis showed that epoxidation changed the copolymer architecture into stars with fewer arms. The copolymers showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
93
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(104 citation statements)
references
References 22 publications
(32 reference statements)
9
93
0
Order By: Relevance
“…In consistence with the literature works (such as Serrano et al 2004, Liu et al 2009, 2009a, nanostructured morphologies were observed by transmission electron microscopy (TEM) and X-ray analysis (Adhikari et al 2012, in preparation).…”
Section: Ftir Spectroscopysupporting
confidence: 55%
See 4 more Smart Citations
“…In consistence with the literature works (such as Serrano et al 2004, Liu et al 2009, 2009a, nanostructured morphologies were observed by transmission electron microscopy (TEM) and X-ray analysis (Adhikari et al 2012, in preparation).…”
Section: Ftir Spectroscopysupporting
confidence: 55%
“…literatures (Serrano et al 2004& Antonietti et al 1996. One gram of the BCP was dissolved in 10 millilitre of dichloromethane in 100 millilitre three-necked round bottom flask equipped with a magnetic stirrer, thermometer and maintained under inert atmosphere.…”
Section: Epoxidation Of Block Copolymersmentioning
confidence: 99%
See 3 more Smart Citations